The prevention and management of Crohn's disease postoperative recurrence: results from the Y-ECCO/ClinCom 2019 Survey. Issue 8 (August 2020) - Dragoni, Gabriele; Ding, Nik; Gecse, Krisztina B.; Mansfield, John C.; Kopylov, Uri; Beaugerie, Laurent; Bossuyt, Peter; Sebastian, Shaji; Milla, Monica; Bagnoli, Siro; Yassin, Nuha A.; Bettenworth, Dominik; et al.
Abstract : Background: Prevention and management of postoperative recurrence (POR) is a controversial field in Crohn's disease. The aim of this survey was to report common practice in real-life settings. Methods: An 11-question survey was distributed among gastroenterologists attending the 14th European Crohn's and Colitis Organisation (ECCO) congress. Results: Postoperative endoscopy to assess recurrence was routinely performed within 12 months by 87% of respondents. Forty-six percent of clinicians reported to maintain endoscopic assessment in routine follow-up even after first negative colonoscopy. Most respondents (60%) considered starting postoperative immunoprophylaxis in naïve patients if one or more known risk factors were present. The number of risk factors was an important driver for prescribing biologics over immunosuppressants for 60% of respondents. In case of fistulizing phenotype, perianal disease, or concomitant colonic involvement, the majority of physicians reported to start an immediate prophylaxis in 85, 98 and 88% of patients, respectively. A significant percentage of clinicians were more prone to an endoscopy-driven treatment in long-standing disease after failure of thiopurines (51%) and elderly (43%). Conclusion: Endoscopy within the first year after surgery to assess POR has become routine in most centres. The high rate of early prophylaxis with expensive biologics despite missing solid evidence highlights the need for more randomized trials. Abstract : Supplemental Digital Content is available in the text.